A new mixed-mode quadrature oscillator using a single CCCDTA - Lamun, Panit; Phasukkit, Pattarapong; Kumngern, Montree; Dejhan, Kobchai (My University, 2011)
This paper presents a new current-controlled mixed-mode quadrature oscillator using only a current controlled current differencing transconductance amplifier (CCCDTA), two grounded capacitors and one MOS resistor. The structure is beneficial to monolithic integrated circuit implementation. The proposed circuit provides two quadrature voltage outputs and two quadrature current outputs. The quadrature current outputs also offer the feature of high output impedance. The oscillation condition and the oscillation frequency of the oscillator are independently controllable. PSPICE simulation results which confirm the theoretical predictions are also given. © 2011 IEEE.
Keywords: current controlled current differencing transconductance amplifier (CCCDTA); mixed-mode circuit; quadrature oscillator